O cultivo da solidariedade na concepção de um grupo de docentes: uma reflexão a partir do pensamento complexo - Santana, Alexsandro Junior de (2014)
The present research takes as study object, the cultivation of solidarity, managed from the complex thinking approach. To realize this task, the discussion aimed to: understand how teachers cultivate solidarity in their subjects; identify the concept of solidarity present in the school, from the pedagogical project, and to analyze how ethics proposed by Edgar Morin reflects on solidarity. The research methodology used to achieve these tasks was bibliographic and documental review; field work; application of semi-open questionnaires, and interviews with six teachers from different subjects within a public school in São Paulo. It was also possible to relate to contexts that interact with the school and that directly affect its dynamics, as in the case of family dislocation, drug trafficking and racial prejudice. The result revealed that solidarity remains a human value taught, cultivated and practiced at school, and despite the challenges of violence, political neglect and human misunderstandings, teachers continue in their exercises, seeking to develop humanizing practice.